PENGARUH INVESTASI TERHADAP KESEMPATAN KERJA DI SUMATERA UTARA - Syafaruddin Munthe (CV. Denasya Smart Publisher, 2024)
This research aims to analyze the influence of exogenous variables on endogenous variables, namely investment and employment opportunities. This type of research is quantitative analysis using secondary data with a time series from 1993 to 2022 obtained from the Central Statistics Agency (BPS) of North Sumatra and Bank Indonesia (BI). The data analysis technique in this research uses a simple regression analysis model. The results of this research show that exogenous variables have a significant effect on endogenous variables in the equation model. The investment variable has a significant effect on the employment opportunity variable. For this reason, it is necessary to increase investment (PMA and PMDN), so that there is a coherent increase in employment opportunities. With increasing investment, job opportunities will expand.